VD_FINDINFO Décision / 2011 / 790 vom 30. September 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, CALOMNIE, MENACEDROIT PÉNAL | 174 ch. 1 CP, 174 CP, 180 al. 1 CP, 319 al. 1 CPP (CH), 319 CPP (CH)